NEED ANALYSIS OF STUDENT WORKSHEET (LKS) OF IONIC EQUILIBRIUM AND pH OF THE SALT SOLUTION BASED ON PROBLEM SOLVING - Faizah, Faizah; Widyastuti, Suciati Rahayu (Jurnal Pendidikan Matematika dan IPA, 2021)
Problem solving skills are one of the skills needed by students in the era of the industrial revolution 4.0, so it becomes a challenge for a teacher to design creative learning. One of the media that supports students' problem solving skills is to use worksheets. Meanwhile, the worksheets used so far are general in nature. Suitable worksheets are developed that support students in solving problems, namely problem solving-based worksheets. This study aims to analyze the need for problem solving-based student worksheets. This type of research is a qualitative descriptive study. This needs analysis is part of the research and development of the 4D model, specifically the Define stage. The subjects in this study were students of class XII in SMA Negeri 3 Cirebon City and chemistry teachers as informants. The results showed that students needed worksheets that were more attractive and easy to understand. The worksheets available are in accordance with KD, KI and the 2013 curriculum, but not yet according to student needs. Based on data obtained from several analyzes including analysis of student perceptions, teacher perceptions, student characteristics, curriculum, assignments, concepts and analysis of learning objectives. So it is necessary to develop problem solving worksheets, especially in the matter of ionic equilibrium and pH of salt solutions which can train students to solve problems and relate theory to facts in everyday life.